Therapeutic Role of Gastrograffin in Adhesive Small Bowel Obstruction After Unsuccessful Conservative Treatment - Shahid, MD Alam; Bhatta, Pashupati; Raya, Akash; Rai, Binod Kumar (Med Phoenix, 2020)
Background: The management of adhesive small bowel obstruction is quite debatable. Gastrograffin, a water-soluble hyperosmolar contrast is used as a diagnostic tool widely but it also has impressive therapeutic role. Hence this study was to determine its therapeutic role in management of adhesive bowel obstruction after failure of conservative treatment. Methods: This cross-section observational study of 42 patients was conducted in 1-year duration from 01 July 2018 to 30 June 2019 using non-probability purposive sampling technique. All the patients were first managed conservatively for 48 hrs, and then given 100ml of gastrograffin through NG tube and clamped. Appearance of dye in cecum on radiograph at different time frame (4, 8, 12 and 24 hours of administration) signifies the success and who failed to do so within 24 hrs. were planned for laparotomy. Results: A total of 42 patients with their age ranged 14-80 years (mean 44.6) were included. Among them 32 (76.19%) were male and 10 (23.80%) female. Most had open appendectomy followed by gynaecological surgery and exploratory laprotomy. Majority had midline incision followed by gridiron and pfanensteil incision. After 8 hrs of gastrograffin administration, it was positive in 12 patients while 19 had at 24 hrs. Total 31 patients showed complete resolution, while remaining 11 showed no improvement and undergone exploratory laparotomy. Conclusion: Thus, the administration of gastrograffin is an effective approach in the management of adhesive small bowel obstruction after failed conservative management and prevents surgeries.